Analisis Pola Komunikasi Tiap Paslon pada Debat Ke-5 Calon Presiden Calon Wakil Presiden Republik Indonesia Tahun 2024 - Aefra Christian Menjang; Nurdiansyah Nurdiansyah; Iman Mukti (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Political debates are one of the main elements in the flow of democracy in various countries, including Indonesia. In the context of the general election held by presidential and vice presidential candidates in 2024, the 5th debate is a crucial moment in the political campaign. This study aims to analyze the various communication patterns carried out by each presidential and vice presidential candidate pair in the 5th debate in 2024. The content analysis method is used to identify and analyze the communication methods used by the candidate pairs. Data were obtained from debate transcriptions and analyzed qualitatively to reveal communication patterns, including word choice, speaking style, use of rhetoric, framing, and argumentation strategies. The results of the study show variations in communication patterns between candidate pairs. Each candidate pair uses different communication strategies in their efforts to influence public opinion. Differences in the use of language, rhetoric, and message focus were found between the candidate pairs, reflecting differences in their campaign strategies. This study contributes to the understanding of the dynamics of political communication in the context of political debates in Indonesia. The results of the analysis can provide valuable insights into the understanding of political communication strategies in the democratic process, and provide a foundation for subsequent researchers in this scientific field.